Pelatihan Berbasis Metakognisi dan Prospeksi Dalam Mengatasi Permasalahan Pengendalian Diri - Muhammad Irfan Nursalam; Anna Rozana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
One of the important skills that students must be able to face academic challenges with adaptation is self-control skills. In one elementary school in Bandung, there is a problem where some students have low self-control skills. This can be seen from the low ability of students to be able to choose activities related to the academic field, such as studying, doing assignments. These students tend to choose activities outside more often of their responsibilities in the academic field, so that it has an impact on low learning awareness, low willingness to do assignments and activities related to academics. So, the purpose of this service activity is to provide metacognition and prospection-based training to help develop self-control skills in 6th grade elementary school students. This activity is carried out in the form of providing material, and opportunities to practice in situations related to metacognition, prospecting, and self-control in elementary school students. Based on the evaluation of the training activities, there was an increase in participants' understanding and skills in prospecting, metacognition, and self-control. It is hoped that this increase can help students to be more self-controlled in facing and solving academic challenges at school.Salah satu keterampilan yang penting dimiliki siswa agar dapat menghadapi tuntutan akademik dengan adaptif adalah keterampilan pengendalian diri. Di salah satu SD di kota Bandung terdapat permasalahan dimana beberapa siswanya memiliki keterampilan pengendalian diri yang rendah. Hal ini terlihat dari rendahnya kemampuan siswa untuk bisa memilih kegiatan yang berkaitan dengan bidang akademik, seperti belajar, mengerjakan tugas. Siswa-siswa ini cenderung lebih sering memilih kegiatan di luar tanggung jawabnya di bidang akademik, sehingga berdampak pada rendahnya kesadaran belajar, rendahnya kemauan untuk mengerjakan tugas dan kegiatan yang berkaitan dengan akdemik. Sehingga tujuan dari kegiatan pengabdian ini adalah memberikan pelatihan berbasis metakognisi untuk membantu mengembangkan keterampilan pengendalian diri pada siswa kelas 6 SD. Kegiatan pelatihan ini dilaksanakan dalam bentuk pemberian materi, dan kesempatan berlatih dalam situasi simulasi berkaitan dengan metakognisi, prospeksi, dan pengendalian diri pada siswa SD. Berdasarkan pengukuran evaluasi kegiatan pelatihan, terdapat peningkatan pemahaman dan keterampilan di area prospeksi, metakognisi, dan pengendalian diri pada peserta. Diharapkan peningkatan tersebut dapat membantu siswa agar lebih bisa mengendalikan diri dalam menghadapi dan menyelesaikan tuntutan akademik di sekolah.